2021
DOI: 10.1016/j.ijporl.2020.110539
|View full text |Cite
|
Sign up to set email alerts
|

Subtle olfactory dysfunction after SARS-CoV-2 virus infection in children

Abstract: Objectives Anosmia/hyposomia have been described as early signs of COVID-19 infection in adults, including young asymptomatic patients who commonly refer olfactory disfunction as their only clinical manifestation. Very few studies involving paediatric age patients have been published until now. This study aims to determine the presence of olfactory dysfunction in children with COVID-19 infection through the use of a self-reported questionnaire and a new olfactory screening tool. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
0
24
0
3
Order By: Relevance
“…A total of 18 studies reported prevalence of smell and/or taste dysfunction, most of them reported more than one type of prevalence among children with COVID-19. Specifically, 11 of the included studies reported the prevalence on smell dysfunction ( 13 , 25 , 27 , 28 , 30 , 34 36 , 40 ), 9 of the included studies reported prevalence on taste dysfunction ( 13 , 27 , 28 , 32 , 34 , 37 , 38 , 40 ), 10 of the included studies reported prevalence on smell or taste dysfunction ( 13 , 14 , 25 , 26 , 28 , 29 , 31 , 33 , 36 , 39 ), and 2 of the included studies reported prevalence on smell and taste dysfunction ( 13 , 28 ). Thus, four different types of prevalence were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 18 studies reported prevalence of smell and/or taste dysfunction, most of them reported more than one type of prevalence among children with COVID-19. Specifically, 11 of the included studies reported the prevalence on smell dysfunction ( 13 , 25 , 27 , 28 , 30 , 34 36 , 40 ), 9 of the included studies reported prevalence on taste dysfunction ( 13 , 27 , 28 , 32 , 34 , 37 , 38 , 40 ), 10 of the included studies reported prevalence on smell or taste dysfunction ( 13 , 14 , 25 , 26 , 28 , 29 , 31 , 33 , 36 , 39 ), and 2 of the included studies reported prevalence on smell and taste dysfunction ( 13 , 28 ). Thus, four different types of prevalence were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis of the data from Tong et al showed the prevalence of olfactory and gustatory dysfunctions in infected adults of 52.7% and 43.93%, respectively [ 13 ]. However, a lower prevalence has been detected in children as described by Concheiro-Guisan et al, which showed that 15% of infected children, aged 11 and older, reported having anosmia [ 15 ]. In our study, 10.4% and 13.1% of children aged 7-15 years old experienced smell and taste disturbances, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The older group in our study reported having taste disturbances significantly more frequently than the group including children between 7 to 10 years of age, with the prevalence of 17.2% and 9.8%, respectively. The lower rates of olfactory and gustatory dysfunctions in pediatrics might be explained by the milder disease course as well as the receptor immaturity [ 15 ]. Studies showed that the sustentacular cells of the olfactory epithelium, which are suggested to have a role in virus entry, are increasing in number as age increases in animal models [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gejala Covid-19 yang relatif ringan pada anak-anak akan mudah untuk dilewatkan untuk diagnosis pada tahap awal ketika muncul. Selain itu, berdasarkan penelitian terbaru pada bulan Desember 2020 yang dilakukan oleh Guisan et al (2020), telah ditemukannya gejala lain diantara anak-anak yang terinfeksi, 5/33 (15%) sampel penelitian disebut menderita tanda-tanda klinis anosmia setelah timbulnya infeksi. Apabila berada di daerah epidemi, kemungkinan infeksi SARS-CoV-2 harus dicurigai terutama bagi anak yang menunjukkan gejala riwayat demam atau riwayat kontak dekat dengan kasus terkonfirmasi (Cai et al, 2020).…”
Section: Gejala Covid Pada Anakunclassified